IDENTIFIKASI KEANEKARAGAMAN DAN SEBARAN JENIS BURUNG UNTUK PENGEMBANGAN EKOWISATA BIRD WATCHING DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG - Asrianny Asrianny; Hendra Saputra; Amran Achmad (PERENNIAL, 2018)
This study aims to identify the diversity and distribution of birds species for bird watching ecotourism development in the Bantimurung Bulusaraung National Park. Field works was conducted in three months, from October to in December 2012. Data collection, was done with line transect method at Leang-Leang, Pattunuang, and Karaenta. Geographical position of transect line (traces) was recorded by using GPS then processed with GIS in order to produced bird watching maps tourist track. Result soft his study showed that, there are 47 species of birds found in the three lines of observation track, and 23 of them (48.9%) was endemic to the island of Sulawesi. Diversity indices of birds on the observation track at Leang-Leang is 3.02, in Pattunuang 2.78, and in the Karaenta 2.25. Among the three lines of observation, the highest population abundance is at Leang-Leang tracking line. It’s equal to 29 individuals /ha while the lowest population abundance are on the Karaenta track with 9 individuals /ha. Key words: Bantimurung Bulusaraung National Park, Bird Watching, Ecotourism